2007
DOI: 10.1074/jbc.m702225200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Progression Locus-2 Is a Critical Regulator of Pancreatic and Lung Inflammation during Acute Pancreatitis

Abstract: Pancreatic and lung inflammation during acute pancreatitis is a poorly understood, but clinically important, phenomenon. The proto-oncogene Tpl2 (tumor progression locus-2) has recently been shown to have important immunomodulatory effects on some inflammatory processes, but its importance to pancreatitis has not been previously examined. Our studies were designed to (a) define the effects of Tpl2 on pancreatic and lung inflammation during pancreatitis and (b) identify mechanisms and cell types responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
5
38
1
Order By: Relevance
“…the ease of controlled pancreatic duct infusion), and it has not been employed in studies using mice. In recently published studies, however, we have shown that the sodium taurocholate model can, in fact, be adapted for use in mice (3) and that the use of this model in genetically modified mouse strains can provide valuable insights into mechanistic issues related to pancreatitis (4). Virtually all of our observations characterizing this bile salt-in-duced pancreatitis model have been confirmed in a series of studies recently reported by Wittel et al (5).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…the ease of controlled pancreatic duct infusion), and it has not been employed in studies using mice. In recently published studies, however, we have shown that the sodium taurocholate model can, in fact, be adapted for use in mice (3) and that the use of this model in genetically modified mouse strains can provide valuable insights into mechanistic issues related to pancreatitis (4). Virtually all of our observations characterizing this bile salt-in-duced pancreatitis model have been confirmed in a series of studies recently reported by Wittel et al (5).…”
supporting
confidence: 63%
“…Small pancreatic acini (1-10 cells per cluster) used to evaluate calcium transients or lactate dehydrogenase leakage were filtered through a 40-m Nitex filter. For preparation of pancreatic fragments, freshly harvested portions of pancreas were minced, in the absence of collagenase, to create small (Ͻ0.2-mm 3 ) pieces as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of pancreas homogenates demonstrate that caerulein activation of ERK, JNK and AP-1 is dependent on TPL-2 expression, as is the induction of MCP-1 (monocyte chemotactic protein-1), MIP-2 (macrophageinflammatory protein-2) and IL-6 [85]. Thus, TPL-2 may regulate pancreatic inflammation during pancreatitis by mediating proinflammatory signals and the generation of neutrophil chemoattracting factors.…”
Section: Regulation Of Immune and Inflammatory Responses By Tpl-2mentioning
confidence: 99%
“…For example, TPL-2 positively regulates the development of pancreatic and lung inflammation during caerulein-induced acute pancreatitis [85]. By generating bone marrow chimeras, pancreatic inflammation was shown to be controlled by TPL-2 in non-myeloid cells.…”
Section: Regulation Of Immune and Inflammatory Responses By Tpl-2mentioning
confidence: 99%
“…Cot/tpl2 is required to process pre-TNF␣ to its mature secreted form in LPS-stimulated macrophages (24). In addition, in different isolated cell types Cot/tpl2 controls the secretion of other cytokines and chemokines such as IL-8, MCP-1, MIP-1␤, KC,10,[24][25][26][27]. Moreover, Cot/tpl2 activation is necessary for the production of PGE 2 in LPS-stimulated macrophages (9).…”
mentioning
confidence: 99%